As influências da tecnologia quanto à preservação da memória: uma análise reflexiva sobre a digitalização de documentos permanentes no Arquivo Central da Universidade Federal da Paraíba - Moura, Gigliolla de Lourdes Batista (2021)
Institutional memory is in constant evolution, as its presence is increasingly required in organizational settings. However, the challenges of how to survive amid so many requirements of elimination and technological diversification, make the memory of institutions find themselves on a fine line between deletion and preservation. In this sense, it is necessary to understand the importance of the archive and the memory aspects that involve them, relating them to technological innovations. This research presents as a question: How does the digitization of permanent documents from the UFPB Central Archive contribute to the preservation of institutional memory? In this context, a preservation of the institutional memory of the Central Archive can contribute so that memory is known through the archive. The general objective of this research is to reflect on the digitization of permanent documents from the UFPB Central Archive and its contribution to the preservation of institutional memory. The specific objectives are based on Understanding a Document Temporality Table - TTD implementation and Decree No. 10.278 (which technical procedures and requirements for digitizing public or private documents) for the procedures for digitizing permanent documents of the Archive UFPB Center; Categorize the permanent documents contained in the UFPB Central Archive to be digitized, in accordance with the TTD and Decree No. 10.278; Verify the effective procedures of the permanent documents digitization process and its relation with the institutional memory. The logical basis of this investigation is based on the hypothetical deductive method, the methodological procedures regarding the objectives based on descriptive and exploratory research. Functionalism is the reference theory for the definition and definition of concepts and hypotheses. The research stands out as bibliographical and documentary. The survey also uses content analysis (CA) to analyze the data collected by the interview. Regarding the final considerations, the Central Archive shows dedication in trying to follow the procedures obtained by Decree No. 10.278, as well as the UFPB Temporality Table, to carry out the process of digitizing permanent documents. However, the archive lacks technical and technological conditions in relation to the preservation of institutional memory. One of the limitations pointed out regarding the preservation of memory is the inexistence of a reliable digital repository for the storage of permanent digitized documents, therefore, in this way, it will not be possible to preserve the institution's memory in the long term, since it is necessary to use of digital repositories, as it is possible to have informational control, reliability and document integrity, so that it is possible to provide dissemination and access, since, without these attributes, the institution cannot be known in its elapsed times. The absence of a reliable digital repository can point to a silencing of institutional memory, as the permanent digitized documents are not being preserved for the future, there is no long-term preservation, which can lead to the loss of the institution's memory.